Growth Of Veronica Miller's Personality In Julie Anne Robinson's The Last Song Movie (2010): A Psychoanalytic Approach - Mahfudho, Mahfudho, Drs. Abdillah Nugroho, M.Hum, Titis Setyabudi, S.S, M.Hum (2013)
This research investigated how is growth of Veronica Miller's Personality in Julie Anne Robinson's The Last Song movie (2010) especially viewed from psychoanalytic approach. The objectives of the research are to analyze the film based on its structural element and to analyze the film based on the psychoanalytic approach. The research paper belongs to the qualitative research. The object of the study is the growth of Veronica Miller's personality reflected in The Last Song movie. The data source comes from primary data source that is The Last Song movie directed by Julie Anne Robinson realized in 2010. While the secondary data sources are other materials taken from books, encyclopedia, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. Firstly, based on the structural analysis of each elements, it shows that the character and characterization, plot, point of view, theme, intent, mise-en scene, cinematography, editing, sound, cast are related to each other and form the unity into good quality movie, secondly, based on psychoanalytic analysis this movie, Julie Anne Robinson illustrated the power of love could change hatred, misunderstanding that causes hatred, and hatred that ends regret.